Severe hepatic injury in interleukin 18 (IL-18) transgenic mice: a key role for IL-18 in regulating hepatocyte apoptosis in vivo. (11th February 2004) - Finotto, S; Siebler, J; Hausding, M; Schipp, M; Wirtz, S; Klein, S; Protschka, M; Doganci, A; Lehr, H A; Trautwein, C; Khosravi-Fahr, R; Strand, D; et al.
Abstract : Background: Interleukin 18 (IL-18) is a cytokine with pleiotropic activity that augments T helper 1 responses and cytotoxic activity of natural killer cells. Methods: To assess the function of IL-18 in vivo, we generated IL-18 transgenic (IL-18 Tg) mice under the control of a CD2 promoter/enhancer construct. Results: Macroscopically, IL-18 Tg mice showed reduced relative liver weight compared with wild-type littermates. TUNEL assays demonstrated increased hepatocyte apoptosis, and primary hepatocytes isolated from IL-18 Tg mice exhibited an increased spontaneous apoptosis rate. Furthermore, cross linking of Fas increased significantly the apoptosis rate in hepatocytes isolated from wild- type mice but to a much lesser extent in IL-18 Tg mice, suggesting spontaneous activation of the Fas pathway in the latter mice. In fact, in vivo blockade of Fas signal transduction by an adenovirus overexpressing the dominant negative form of the Fas associated death domain rescued hepatocytes from undergoing apoptosis. Finally, adoptive transfer of CD4 + T cells from IL-18 Tg mice but not from wild-type littermates in SCID mice resulted in severe liver failure with massive periportal fibrosis due to hepatocyte apoptosis. Conclusion: IL-18 plays a fundamental role in regulating hepatocyte apoptosis. Furthermore, our transgenic model provides a novel tool to study the mechanisms of IL-18 dependent liver injury in vivo.